Kinerja Keuangan Perbankan Syariah Sebelum dan Selama Pandemi Covid-19 - Awaluddin, Murtiadi; Anisa, Nur; Sijal, Mutakallim; Dian, Dian; Tuarita, Adam (Study of Scientific and Behavioral Management, 2023)
This research focuses on the financial performance between Bank BTPN Syariah and Bank Panin Dubai Syariah before and during the COVID-19 pandemic period. The method used is a quantitative approach using the Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) ratio as the main indicators. The data analyzed covers the period 2018 to 2021 for the two banks. Testing was carried out four times to obtain a comprehensive understanding. First, the dependent sample t-test was carried out at Bank BTPN Syariah, comparing performance before and during the pandemic. Second, the dependent sample t-test was carried out at Bank Panin Dubai Syariah, to compare performance before and during the pandemic. Third, an independent sample t-test was carried out to compare Bank BTPN Syariah with Bank Panin Dubai Syariah before the pandemic. Finally, an independent sample t-test was carried out to compare the two during the pandemic.The research results show that there is no significant difference in the ROA of Bank BTPN Syariah before and during the pandemic, while the CAR and NPF have a significant difference where the CAR and NPF during the pandemic have increased more than before the pandemic. The ROA and NPF of Bank Panin Dubai Syariah before and during the pandemic did not have a significant difference, while there was a significant difference in the CAR. Before and during the pandemic, there were significant differences between the ROA, CAR and NPF of Bank BTPN Syariah and Bank Panin Dubai Syariah.Suggestions for future researchers are to increase the ratio and periodization of the data so that they can get different research results